EDUCATION BETWEEN IDEOLOGY AND INSTRUCTION: reassessing Freirean pedagogy through theory, evidence, and comparison - Araújo Junior, Antonio Henriques de; Viagi, Arcione Ferreira (Revista Ciências Exatas, 2026)
Paulo Freire’s work occupies a hegemonic position in Brazilian educational thought and has increasingly functioned not only as a theoretical reference, but as a normative framework shaping public policy and teacher education. This article offers a critical reappraisal of that dominance, explicitly distinguishing academic analysis from political or ideological polemic. It argues that Freirean pedagogy entails a structural subordination of pedagogy to politics, weakening the epistemic status of accumulated knowledge, displacing systematic instruction, and producing adverse learning outcomes—particularly for students from lower socioeconomic backgrounds. Employing a threefold methodology that integrates theoretical analysis, empirical evidence, and international comparison, the study examines the epistemological foundations of Freirean pedagogy, the pedagogical role attributed to dialogue, Brazilian educational performance indicators, and contrasts with high-performing educational systems. The article concludes that the sacralization of Freire’s work constrains pedagogical debate, shields instructional practices from empirical evaluation, and risks reproducing the very cognitive inequalities that critical pedagogy seeks to overcome.